PENGARUH KEMASAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN WARDAH: STUDI KASUS PADA KONSUMEN WARDAH MUTIARA COSMETICS YOGYAKARTA - Qurrata Ayunina Ciptantri Hadipranata; Renanda Pradina Sumardi (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to determine the effect of packaging and product quality on purchasing decisions of Wardah consumers at Mutiara Cosmetics Yogyakarta. The population in this study is Wardah consumers who have made purchases at Mutiara Cosmetics Yogyakarta, totaling 100 people. The sample used in the study were all respondents totaling 100 people. The instrument of this research is a questionnaire that has been tested for validity and reliability. The data analysis technique used multiple regression. The results showed that: (1) packaging had a positive effect on the purchasing decisions of Wardah consumers at Mutiara Cosmetics Yogyakarta, namely the t value = 4.370; significance value 0.000less than0.05; and regression coefficient = 0.406. (2) product quality has a positive effect on the purchasing decisions of Wardah consumers at Mutiara Cosmetics Yogyakarta, namely the value of t count = 3,841; significance value 0.000less than0.05; and regression coefficient = 0.375. (3) packaging and product quality have a joint effect on the purchasing decisions of Wardah consumers at Mutiara Cosmetics Yogyakarta, namely the calculated F value = 47,673 with a significance of 0.000 less than 0.05.